A Thermomorphic Polyethylene‐Supported Imidazolium Salt for the Fixation of CO2 into Cyclic Carbonates. Issue 8 (5th March 2020) - Grollier, Kevin; Vu, Nam Duc; Onida, Killian; Akhdar, Ayman; Norsic, Sébastien; D'Agosto, Franck; Boisson, Christophe; Duguet, Nicolas
Abstract: An imidazolium catalyst supported on thermomorphic polyethylene (PE) was prepared from 1‐methylimidazole and polyethylene iodide (PE−I). The catalyst was characterized by 1 H and 13 C NMR, SEC and MALDI‐ToF mass spectrometry. Its catalytic activity was evaluated in the ring‐opening of epoxides with carbon dioxide to give cyclic carbonates under solvent‐free conditions. The catalyst proved to be active at low catalyst loading (down to 0.1 mol%) and allows the reaction to occur at low CO2 pressure (1–5 bar) and moderate temperature (100 °C). A range of terminal and internal epoxides was converted to the corresponding cyclic carbonates with high yields and selectivities. The recyclability of the catalyst was studied and no significant loss of activity was observed after 5 runs. Abstract :